Efektifitas Pakan Daun Kelor Terhadap Kualitas Protein Telur Puyuh (Jurnal Ilmu Pendidikan dan Sains: Visioedusains, 2025)
This study aims to analyze the effect of adding moringa leaf flour (Moringa oleifera) in feed on the quality of quail eggs (Coturnix coturnix japonica). Two treatment groups were used, namely the control group given standard feed (BR) and the experimental group received a mixture of BR and moringa leaf flour. The experimental feed formulation consisted of corn flour, rice bran, fish flour, and moringa leaf flour with a ratio of 1:1:1:1. Feeding was carried out twice a day with a dose of 200 grams. The results showed a significant increase in the egg weight of the experimental group (average 12.89 g) compared to the control group (average 11.24 g), with an average increase reaching 20%. Analysis of protein content showed that eggs from the experimental group had higher protein content (13.83–15.48%) than the control group (12.11–13.66%). In addition, there were indications of a decrease in cholesterol levels in the experimental group, supported by the high protein content and bioactive compounds in moringa leaves. These findings indicate that moringa leaf flour can significantly increase the nutritional value and health of quail eggs, and has the potential to be an effective and functional alternative to poultry feed.